Alternative use of suvorexant (Belsomra®) for the prevention of alcohol drinking and seeking in rats with a history of alcohol dependence - Flores-Ramirez, Francisco J.; Illenberger, Jessica M.; Pascasio, Glenn E.; Matzeu, Alessandra; Mason, Barbara J.; Martin-Fardon, Rémi (Frontiers in Behavioral Neuroscience, 2022)
Alcohol use disorder (AUD) is one of the most treatment-resistant medical conditions globally. The orexin (Orx) system regulates diverse physiological processes, including stress, and is a system of interest for the development of pharmaceuticals to treat substance use disorders, particularly AUD. The present study tested the ability of the dual orexin receptor antagonist suvorexant (SUV), marketed by Merck as Belsomra®, for the treatment of insomnia, to decrease alcohol self-administration and the stress-induced reinstatement of alcohol-seeking behavior in male Wistar rats with a history of alcohol dependence. Rats were trained to orally self-administer 10% alcohol (30 min/day for 3 weeks) and were either made dependent via chronic intermittent alcohol vapor exposure (14 h ON, 10 h OFF) for 6 weeks or exposed to air (nondependent). Starting on week 7, the effect of SUV (0-20 mg/kg, p.o.) was tested on alcohol self-administration at acute abstinence (8 h after vapor was turned OFF) twice weekly. A separate cohort of rats that were prepared in parallel was removed from alcohol vapor exposure and then subjected to extinction training for 14 sessions. Once extinction was achieved, the rats received SUV (0 and 5 mg/kg, p.o.) and were tested for the footshock stress-induced reinstatement of alcohol-seeking behavior. Suvorexant at 5, 10, and 20 mg/kg selectively decreased alcohol intake in dependent rats. Furthermore, 5 mg/kg SUV prevented the stress-induced reinstatement of alcohol-seeking behavior in dependent rats only. These results underscore the significance of targeting the Orx system for the treatment of substance use disorders generally and suggest that repurposing SUV could be an alternative approach for the treatment of AUD.